Biomimetic Composite Scaffold With Phosphoserine Signaling for Bone Tissue Engineering Application - Salgado, Christiane Laranjo; Teixeira, Beatriz Isabel Brites; Monteiro, Fernando Jorge Mendes (Frontiers in Bioengineering and Biotechnology, 2019)
In guided bone tissue engineering, successful ingrowth of MSCs depends primarily on the nature of the scaffold. It is well known that only seconds after implantation, biomaterials are coated by a layer of adsorbed proteins/peptides which modulates the subsequent cell/scaffold interactions, especially at early times after implantation. In this work, nanohydroxyapatite and collagen based composite materials (Coll/nanoHA) were modified with phosphorylated amino acid (O-phospho-L-serine – OPS) to mimic bone tissue and induce cell differentiation. The choice for this phosphorylated amino acid is due to the fact that osteopontin is a serine-rich glycol-phosphoprotein and has been associated to the early stages of bone formation and regeneration. Several concentrations of OPS were added to the Coll/nanoHA scaffold and physico-chemical, mechanical and in vitro cell behavior were evaluated. Afterwards, the composite scaffold with stronger mechanical and best cellular behavior was tested in vivo, with or without previous in vitro culture of human MSC’s (bone tissue engineering). The OPS signaling of the biocomposite scaffolds showed similar cellular adhesion and proliferation, but higher ALP enzyme activity (HBMSC). In vivo bone ectopic formation studies allowed for a thorough evaluation of the materials for MSC’s osteogenic differentiation. The OPS-scaffolds results showed that the material could modulated mesenchymal cells behavior in favor of osteogenic differentiation into late osteoblasts that gave raised to their ECM with human bone proteins (osteopontin) and calcium deposits. Finally, OPS-modified scaffolds enhanced cell survival, engraftment, migration and spatial distribution within the 3D matrix that could be used as a cell-loaded scaffold for tissue engineering applications and accelerate bone regeneration processes.